2021
DOI: 10.1002/alz.050212
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of neuroEPO in mild‐to‐moderate Alzheimer’s disease

Abstract: Background: NeuroEPO, a nasal pharmaceutical solution of recombinant human erythropoietin with low sialic acid, was in clinical development for the treatment of mildmoderate Alzheimer's disease. Method:A double-blind, randomized, placebo-controlled, multicenter, prospective, with adaptive design, phase II/III clinical trial involving 174 patients with mild-tomoderate Alzheimer's, was conducted. NeuroEPO or placebo, with different doses, was administered by nasal route 3 times a weeks for 48 weeks. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recent studies have shown that NeuroEPO administered intranasally has a neuroprotective effect on different models of neurological diseases (1,2,3,4,8) . This neuroprotective effect has also been demonstrated in controlled clinical trials in Parkinson's and Alzheimer's disease (9,10) . However, it is not known whether its intranasal application at maintained doses, for a longer period, could cause alterations in the histological structure of the respiratory mucosa in rats.…”
Section: Introductionmentioning
confidence: 84%
“…Recent studies have shown that NeuroEPO administered intranasally has a neuroprotective effect on different models of neurological diseases (1,2,3,4,8) . This neuroprotective effect has also been demonstrated in controlled clinical trials in Parkinson's and Alzheimer's disease (9,10) . However, it is not known whether its intranasal application at maintained doses, for a longer period, could cause alterations in the histological structure of the respiratory mucosa in rats.…”
Section: Introductionmentioning
confidence: 84%
“… 86 , 87 These are not optimized for delivery to the brain, which is not a major site of EPO production. Nonetheless, given that there is preliminary evidence that EPO treatment may have clinical benefit in treatment of mild to moderate AD, 88 , 89 empirically guided approaches involving boosting EPO levels/oxygen supply to the brain via use of the currently available PHD inhibitors developed for treatment of anemia by the promotion of erythropoiesis may be of interest.…”
Section: Links Between 2ogdd and Admentioning
confidence: 99%